12-12y-3(y+2)=4y+6-y

Simple and best practice solution for 12-12y-3(y+2)=4y+6-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-12y-3(y+2)=4y+6-y equation:


Simplifying
12 + -12y + -3(y + 2) = 4y + 6 + -1y

Reorder the terms:
12 + -12y + -3(2 + y) = 4y + 6 + -1y
12 + -12y + (2 * -3 + y * -3) = 4y + 6 + -1y
12 + -12y + (-6 + -3y) = 4y + 6 + -1y

Reorder the terms:
12 + -6 + -12y + -3y = 4y + 6 + -1y

Combine like terms: 12 + -6 = 6
6 + -12y + -3y = 4y + 6 + -1y

Combine like terms: -12y + -3y = -15y
6 + -15y = 4y + 6 + -1y

Reorder the terms:
6 + -15y = 6 + 4y + -1y

Combine like terms: 4y + -1y = 3y
6 + -15y = 6 + 3y

Add '-6' to each side of the equation.
6 + -6 + -15y = 6 + -6 + 3y

Combine like terms: 6 + -6 = 0
0 + -15y = 6 + -6 + 3y
-15y = 6 + -6 + 3y

Combine like terms: 6 + -6 = 0
-15y = 0 + 3y
-15y = 3y

Solving
-15y = 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-15y + -3y = 3y + -3y

Combine like terms: -15y + -3y = -18y
-18y = 3y + -3y

Combine like terms: 3y + -3y = 0
-18y = 0

Divide each side by '-18'.
y = 0

Simplifying
y = 0

See similar equations:

| x^3+40=13 | | 5e^9t=7e^8t | | 9+6=135 | | 2x+(-7+1x)=-1 | | 3x(x+2)=-18 | | -2(y+2)=3y | | 7s-8=64 | | y=17x^3 | | -14-8-6c=12-4c | | x=.25*150+40 | | 15-4(x+3)=19 | | 0.6h=13.032 | | 8s-8=65 | | Logx=.75 | | 5x-5+4x=-41 | | 3x+(x-5)=-11 | | 7x+2(0)=3 | | H(1)=-16t^2+96t+6 | | 4y-21-9y+35= | | f-32=1.8m | | 60=.25x+40 | | f(x)=x^3-2x+4 | | 1-18v+11=-19v+19 | | g(x)=ln[(7x+4)*5] | | -18-6k=-6(k+3) | | 5y=10-12x | | 6(u+3)=3u+12 | | 8x-9-15= | | 1+19f=6f+7+12f | | 1.5x+1y=10 | | -4(5t-4)+5t=2t-4 | | (6x+y^2)dx+y(2x+3y)dy=o |

Equations solver categories